Some related to pronormality subgroup families and the properties of a group - Kirichenko, V.V.; Kurdachenko, L.A.; Subbotin, I.Ya. (Algebra and Discrete Mathematics, 2011)
Some influential families of subgroups such as pronormal subgroups, contranormal subgroups, and abnormal subgroups, their generalizations, characterizations, interplays between them and the group, and their connections to other types of subgroups have been considered.